2019
DOI: 10.1001/jamanetworkopen.2019.13650
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Pneumococcal Nasopharyngeal Carriage in Very Young Fijian Infants Born by Vaginal or Cesarean Delivery

Abstract: Key PointsQuestionIs pneumococcal nasopharyngeal carriage associated with mode of delivery in Fijian infants aged 5 to 8 weeks?FindingsIn this cross-sectional study, pneumococcal nasopharyngeal carriage prevalence, density, and serotype range were higher in infants delivered vaginally vs cesarean delivery. After adjustment, vaginal delivery was positively associated with pneumococcal nasopharyngeal carriage.MeaningThese findings may be owing to differential exposure to the vaginal microbiota during delivery an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…We excluded infants who were born by caesarian delivery, and were thus unable to evaluate the effects of delivery mode on the nasopharyngeal microbiome or the risk of S. pneumoniae colonization. Interestingly, in a study of >2000 Fijian infants 5-8 weeks of age, the prevalence and density of pneumococcal colonization were higher among infants born by vaginal delivery than among infants delivered by caesarian birth [79]. Comparative analyses of microbiome composition were based on sample relative abundances, and we are thus unable to determine if the observed associations represent differences in the absolute amounts of bacterial genera or species within the nasopharynx across samples.…”
Section: Discussionmentioning
confidence: 90%
“…We excluded infants who were born by caesarian delivery, and were thus unable to evaluate the effects of delivery mode on the nasopharyngeal microbiome or the risk of S. pneumoniae colonization. Interestingly, in a study of >2000 Fijian infants 5-8 weeks of age, the prevalence and density of pneumococcal colonization were higher among infants born by vaginal delivery than among infants delivered by caesarian birth [79]. Comparative analyses of microbiome composition were based on sample relative abundances, and we are thus unable to determine if the observed associations represent differences in the absolute amounts of bacterial genera or species within the nasopharynx across samples.…”
Section: Discussionmentioning
confidence: 90%
“…[36,41,42] of studies from high, upper-middle, lower-middle, and low-income countries, respectively. No single risk factor was assessed for association with carriage in all studies, and some risk factors, such as prematurity [41], malnutrition or body mass index [39, 44, 46, 62], and infant mode of delivery [47,69] were assessed in one or two income classifications only.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Three studies reported ethnicity-based differences in pneumococcal carriage [67,68,100]. One study reported physical contact with toddlers aged 12-23 months [68] and vaginal mode of infant delivery [69] as positively associated with pneumococcal carriage.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…This finding highlights the ongoing importance of environmental public health and improved standards of living. In a separate study, pneumococcal nasopharyngeal carriage was higher among newborns/infants born by vaginal delivery in Fiji than those born by Caesarean section, supporting the hypothesis that vertical pneumococcal transmission occurs through exposure to vaginal microbiome [ 7 ]. The fifth paper from Fiji was an earlier paper reporting the seven-valent PCV [ 11 ].…”
Section: Pcv and The Prevention Of Otitis Media And Hearing Loss Amon...mentioning
confidence: 84%
“…A literature review found seven papers investigating PCV in Pacific Island nations, with 5 from Fiji [ 7 - 11 ], one from Papua New Guinea [ 12 ], and another from Tonga [ 13 ]. Three of the papers from Fiji evaluated the effect of 10-valent PCV introduction in October 2012 and found that results were overall very positive.…”
Section: Pcv and The Prevention Of Otitis Media And Hearing Loss Amon...mentioning
confidence: 99%